Impact of Added Copper and Chlortetracycline on Growth Performance of Nursery Pigs - M. B. Menegat; K. Capps; H. Williams; J. C. Woodworth; S. S. Dritz; R. G. Amachawadi; T. G. Nagaraja; M. D. Tokach; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 320 nursery pigs (DNA 200 × 400 barrows; initially 16.3 lb BW) were used in a 28-d trial to determine the effect of copper (Cu) and chlortetracycline (CTC), fed alone or in combination, on growth performance of weanling pigs. Pigs were weaned at approximately 21 d of age and fed a common pelleted starter diet (non-medicated) for 7 d after weaning. Pigs were allotted to dietary treatments based on BW and location in a randomized complete block design. Dietary treatments were arranged as a 2 × 2 factorial with main effects of added Cu (0 vs. 200 ppm Cu from copper sulfate) and CTC (0 vs. 440 ppm CTC). Experimental diets were corn-soybean meal-based and were fed in one phase for 28 d in meal form. There were 5 pigs per pen and 8 replications per treatment with each replication consisting of a pair of adjoining pens. The results showed no evidence for an interactive effect of Cu and CTC for any of the performance and economic variables (P>0.05). From d 0 to 14, added Cu increased (P<0.05) ADG and ADFI and added CTC improved (P<0.05) ADG, ADFI, and F/G. From d 14 to 28, the addition of CTC to the diet improved (P<0.05) ADG and ADFI, but there was no evidence for a Cu effect. For the overall experimental period (d 0 to 28), pigs fed diets with CTC had improved (P<0.05) ADG, ADFI, and F/G, but there was no evidence for a Cu effect. The inclusion of either Cu or CTC increased (P<0.05) BW on d 14 and 28. Regarding the economics, added dietary Cu increased (P<0.05) feed cost per pig and value of gain per pig, but not income over feed cost (IOFC). The addition of CTC to the diet increased (P<0.05) feed cost per pig, value of gain per pig, and IOFC. In conclusion, the findings of the present study characterize a beneficial effect of feeding Cu for 14 d on growth performance of young pigs (16 to 25 lb) and a positive effect of including CTC in nursery diets. The lack of interactive effects between Cu and CTC suggests that the responses of Cu and CTC on growth performance of nursery pigs are as efficacious when fed alone or in combination.
Keywords: Cu; CTC; feed-grade antibiotic; supplementation; weanling pig